Multimodality imaging methods and systemic biomarkers in classical low-flow low-gradient aortic stenosis: Key findings for risk stratification - Lopes, Maria Antonieta Albanez A. de M.; Campos, Carlos M.; Rosa, Vitor Emer Egypto; Sampaio, Roney O.; Morais, Thamara C.; de Brito Júnior, Fábio Sândoli; Vieira, Marcelo L. C.; Mathias, Wilson; Fernandes, Joao Ricardo Cordeiro; de Santis, Antonio; Santos, Luciano de Moura; Rochitte, Carlos E.; et al. (Frontiers in Cardiovascular Medicine, 2023)
OBJECTIVES: The aim of the present study is to assess multimodality imaging findings according to systemic biomarkers, troponin I (hsTnT) and B-type natriuretic peptide (BNP) levels in low-flow, low-gradient aortic stenosis (LFLG-AS) and reduced left ventricular ejection fraction (LVEF) patients. BACKGROUND: elevated levels of BNP and hsTnT have been related with poor prognosis in patients with LFLG-AS. METHODS: Prospective study with LFLG-AS (LVEF <50%, aortic valve area ≤ 1,0 cm² and mean gradient <40 mm Hg) patients that underwent hsTnT, BNP, coronary angiography, cardiac magnetic resonance (CMR) with T1 mapping, 2 dimensional echocardiogram (2DTTE), 3D echocardiogram (3DTTE) and dobutamine stress echocardiogram (DSE). Patients were divided into 3 groups according to BNP and hsTnT levels: Group 1 BNP and hsTnT levels below median (BNP < 395 pg/ml, < 1.98 folds and TnI-Ultra < 0.042 ng/ml, < 1.8 folds); Group 2 when either BNP or hsTnT higher than median and Group 3 BNP when both hsTnT and BNP were higher than median. RESULTS: 49 patients with LFLG-AS were included (Group 1: 17 patients, Group 2: 14 patients and Group 3: 18 patients). Clinical characteristics (including risk scores) were similar among groups and not able to stratify these groups. Patients with elevation of both biomarkers had lower valvuloarterial impedance (P=0.03), lower Ejection Fraction (P=0.02), less moderate/severe mitral (P=0.01) and tricuspid regurgitation (P<0.01) by 2DTTE. CMR identified a progressive increase (from Group 1 to 3) of right and left chamber volumes (P<0.05); reduction in right and left ejection fraction (P<0.05) and a marked increase in myocardial fibrosis assessed by extracellular volume (ECV) (P=0.03) and indexed extracellular volume (iECV) (P<0.01). CONCLUSIONS: Higher levels of BNP and hsTnI in LFLG-AS patients are associated with worse multi-modality evidence of cardiac remodeling and fibrosis.